A reaction-diffusion methodology for soft object simulation - Zhong, Yongmin; Shirinzadeh, B.; Alici, G.; Smith, J. (ACM, 2006)
In this paper, a new methodology is presented to simulatedeformation of soft objects by the reaction-diffusion analogy. Thepotential energy generated by an external force as a result of adeformation is propagated among mass points by the principle ofreaction-diffusion. The novelty of the methodology is that thereaction-diffusion techniques are established to describe thepotential energy of deformation and to extrapolate internal forcesof a deformed object. An improved reaction-diffusion model isdeveloped for the natural propagation of the energy generated bythe external force. A method is presented to derive the internalforces from the potential energy distribution. The proposedmethodology not only deals with large-range deformation, butalso accommodates both isotropic and anisotropic materials bysimply changing diffusion constants. Examples are presented todemonstrate the efficiency of the proposed methodology.